Tradução e adaptação transcultural da heartland forgiveness scale (Hfs) para idosos brasileiros - Rodrigues, Gabriela Veiga Alano (2019)
The Heartland Forgiveness Scale (HFS) is an instrument which measures the personal disposition for forgiveness toward others, yourself, and situations beyond the control of anyone. As a construct belonging to Positive Psychology, Forgiveness is a process that involves cognitive, emotional, motivational and social tools, and can also be considered a way of caring for others. The present study aimed to translate and transculturally adapt the HFS, presenting its first psychometric properties, adapting the instrument to the elderly Brazilian population. In order to conduce this study, the adaptation method of the instrument was divided into stages: conceptual definitions and literature review; translation and synthesis of translations; backtranslation; expert analysis; pilot study and preparation of the final version of the instrument; inicial psychometric analysis of the instrument final version. Four translators and two specialist psychologists participated in the stages of translation, back-translation and analysis of specialists. The pilot study was attended by 32 elderly people. The instruments used were: Demographic Data Sheet, HFS, , Mini-exame do Estado Mental, Escala de depressão geriátrica (GDS-15) e a Escala de Afetos Positivos e Negativos (PANAS). From this study, although in an initial character, it can be concluded that the HFS is translated into Brazilian Portuguese and is transculturalally adapted to the Brazilian elderly population. Thus, the instrument is apt to be applied in a larger population so that it can be submitted to psychometric analysis of its validation. The construction and adaptation of instruments from other cultures are necessary for the Brazilian reality due to the scarcity of instruments in this subject in the country. In the future, it may also contribute to the elaboration of intervention techniques and the creation of strategies aimed at prevention and promotion of the health of the elderly.